Lead Halide Perovskite‐Based Dynamic Metasurfaces. Issue 7 (11th June 2019) - Zhang, Chen; Xiao, Shumin; Wang, Yuhan; Gao, Yisheng; Fan, Yubin; Huang, Can; Zhang, Nan; Yang, Wenhong; Song, Qinghai
Abstract: Lead halide perovskites CH3 NH3 PbX3 (MAPbX3 ) are known to have high refractive index and controllable bandgap, making them attractive for all‐dielectric and tunable metasurfaces. Till now, perovskite metasurfaces have only been used in structural colors. More interesting meta‐devices with 2π phase control are still absent. Here, MAPbX3 ‐perovskite‐based metasurfaces are experimentally demonstrated with a complete control of phase shift in a reflection mode. By utilizing MAPbBr3 cut‐wires as meta‐atoms on a ground metal film, it is found that the MAPbBr3 perovskite metasurface can produce full phase control from 0 to 2π and high reflection efficiency simultaneously. Consequently, high‐efficiency polarization conversion, anomalous reflection, and meta‐holograms are successfully produced. Most interestingly, the bandgap of the MAPbX3 perovskite can be post‐synthetically and reversibly tuned via anion exchange, providing a new approach to dynamically control of the all‐dielectric meta‐devices with novel function such as anomalous reflection and hologram. Abstract : MAPbX3 ‐perovskite‐based metasurfaces are experimentally demonstrated with a complete control of phase shift. High‐efficiency polarization conversion, anomalous reflection, and meta‐holograms are successfully produced. Most interestingly, the bandgap of the perovskite can be post‐synthetically and reversibly tuned via anion exchange, providing a new approach to dynamically control the all‐dielectric meta‐devices with novel function.